2020
DOI: 10.1029/2020jc016549
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Subinertial Waves Along the Patagonian Shelf Break in a 1/12° Global Operational Model

Abstract: The Malvinas Current (MC), a major western boundary current of the South Atlantic Ocean, is an offshoot of the Antarctic Circumpolar Current (Figure 1a) that flows northward following the Subantarctic Front (SAF) along the eastern continental slope of South America. The MC, which borders one of the widest continental shelves of the world, is strongly controlled by bottom topography. Between 52°S and 49°S, the bottom slope is west-east orientated and gentle (2,000 m over 300 km) and the MC is rather wide (300 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
(49 reference statements)
1
18
0
Order By: Relevance
“…Our analyses suggest that these regions are likely sources 698 of SLAs that propagate in forms of mesoscale structures (or eddies) along the Patagonian slope 699 and modulate the strength of the MC. The estimated propagation velocity and origin of the SLAs 700 derived in this study are in agreement with recent analyses of a numerical model (Poli et al, 2020) i being the mooring number and j standing for the level from the surface (see Figure 2). Here, Ɵ 912 is the angle in degrees of mean velocity direction relative to the geographical north, V (cm s -1 ) is 913 the magnitude of the time-average velocity and v (cm s -1 ) and u (cm s -1 ) are the velocity 914 components, σ is the standard deviation and unless otherwise specified, mean values are indicated.…”
supporting
confidence: 90%
“…Our analyses suggest that these regions are likely sources 698 of SLAs that propagate in forms of mesoscale structures (or eddies) along the Patagonian slope 699 and modulate the strength of the MC. The estimated propagation velocity and origin of the SLAs 700 derived in this study are in agreement with recent analyses of a numerical model (Poli et al, 2020) i being the mooring number and j standing for the level from the surface (see Figure 2). Here, Ɵ 912 is the angle in degrees of mean velocity direction relative to the geographical north, V (cm s -1 ) is 913 the magnitude of the time-average velocity and v (cm s -1 ) and u (cm s -1 ) are the velocity 914 components, σ is the standard deviation and unless otherwise specified, mean values are indicated.…”
supporting
confidence: 90%
“…To keep a homogeneous quality over the entire period, GLORYS12 is restricted to the altimetry era since the observational network before the altimeters' arrival is not informative on mesoscale. Several scientific studies have already investigated thoroughly local ocean processes by comparing the GLORYS12 reanalysis with independent observations campaigns (e.g., Artana et al, 2018;Artana et al, 2019a;Poli et al, 2020;Chenillat et al, 2021;Verezemskaya et al, 2021). The objective of this paper is to provide some hindsight about the global behavior of the reanalysis compared to assimilated or independent observations, with a review of the strengths and weaknesses.…”
Section: Introductionmentioning
confidence: 99%
“…Though crossing 15 (Table 1) occupied in November 2016 did not reach the outer shelf, it shows the inshore and main branches of the MC with maximum velocities of 65 and 71 cm/s, respectively (Figure S11). These two sections across the inshore jet reveal variable velocity of the coastal branch, which may be associated with the presence of recently reported trapped waves in the region (Poli et al, 2020). The relatively low sea level anomalies observed in the main part of the current (red line in Figure 12a) are consistent with the low variability characteristic of this region; though intense eddies are usually observed east ∼58°W (i.e., further offshore from transect 5, e.g., .…”
Section: The MC Along the Western Margin Of The Argentine Basinmentioning
confidence: 51%
“…It was shown that the MC variability is linked with the variability of the ACC and this connection is masked by high-frequency oscillations (Fetter & Matano, 2008). The variability of the inshore branch velocity field is partially caused by the presence of trapped waves in the region (Poli et al, 2020). Internal waves with intense surface manifestations propagate in the opposite direction of the MC (Magalhaes & da Silva, 2017).…”
mentioning
confidence: 99%